Clinical characteristics and prognosis of cardiac amyloidosis defined by mass spectrometry‐based proteomics in an Australian cohort. Issue 1 (20th January 2022) - Withers, Barbara; McCaughan, Georgia; Hayward, Christopher; Kotlyar, Eugene; Jabbour, Andrew; Rainer, Stephen; De Angelis, Enzo; Horvath, Noemi; Milliken, Sam; Dogan, Ahmet; MacDonald, Peter; Moore, John
Abstract: Background: Cardiac amyloidosis has a very poor prognosis, but it is the nature of the involved precursor protein that ultimately dictates treatment and survival. Aim: Definitively characterise the amyloid subtype by mass spectrometry (MS) in an Australian cohort of patients with cardiac amyloidosis. Methods: We report the clinical characteristics and survival of 47 cardiac amyloid patients across two Australian centres including 39 patients evaluated for definitive amyloid subtype utilising laser microdissection and tandem mass spectrometry. Results: A quarter ( n = 12) of patients were classified as wild‐type transthyretin amyloidosis (ATTRwt), 33 patients as light or heavy chain amyloidosis (AL or AH) and two as hereditary mutant transthyretin amyloidosis. Greater left ventricular hypertrophy (interventricular septum 22 vs 15 mm; P = 0.005) and history of cardiac arrhythmia (75% vs 31%; P = 0.016) were significantly associated with ATTRwt patients compared with AL/AH patients. AL patients demonstrated significantly shorter median survival compared with ATTRwt patients (3.5 vs 37 months; P = 0.007). New York Heart Association class III–IV symptoms or plasma cells ≥10% at diagnosis, were the only independent predictors of worse survival in AL patients on multivariate analysis. Conclusions: AL amyloidosis accounted for 68% of our cohort of patients with cardiac amyloidosis while ATTR accounted for 26%. In the era of novel therapies for both AL amyloid and ATTR, identification of the correct amyloid subtype is essential in making therapeutic decisions and providing accurate prognostic information to patients. Laser microdissection and tandem mass spectrometry plays an important role in identifying amyloid subtype, particularly in complex cases.